The Dilemma of Decentralization in Public Policy Implementation in Indonesia - Aulia, Ajeng Putri; Andhini (Indonesian Journal of Public Administration Review, 2025)
Decentralization has been a central agenda in Indonesia's governmental reform since the end of the New Order regime, marked by the enactment of Law No. 22 of 1999, which was later revised through Law No. 23 of 2014 on Regional Government. The primary goals of decentralization are to strengthen local democracy, enhance the effectiveness of public service delivery, and accelerate development based on local needs. However, its implementation has led to a range of complex dilemmas. This article aims to critically examine the dynamics and challenges of decentralization in the context of public policy implementation in Indonesia, with a particular focus on structural issues such as disparities in regional capacity, overlapping authorities between central and local governments, weak intergovernmental coordination, and the growing potential for misuse of autonomy by local actors. This study employs a qualitative approach using literature review and thematic analysis of regulations, academic literature, and relevant empirical studies. The main findings indicate that decentralization, when not supported by institutional readiness and adequate oversight, tends to produce policy fragmentation, widen interregional disparities, and create opportunities for corrupt practices at the local level. Therefore, a reformulation of decentralized approaches is urgently needed through the strengthening of asymmetric decentralization models, improvement of intergovernmental governance mechanisms, and the development of effective and adaptive accountability systems. Without a fundamental correction to the design and practice of decentralization, public policy in Indonesia will continue to face structural obstacles that undermine the quality of local governance and threaten national integration.